Light-controlled swimming robotics designed by 3D printer - Tan, Timothy Zhi Qiang (Nanyang Technological University, 2022)
This project attempts to optimize and procure a robot capable of swimming while guided and powered by light. With the shrinking of technology, and with them, robots, there is a need for non-physical connections that would enable robots to move. This project explores one such possibility in the form of light, thus aiming to develop a soft robot that relies only on light for mobility, without holding complex electronics and wires. This robot will be printed via 3D Bioprinter and made up of soft materials.